Geometry of Ricci and (η,ω)-Ricci solitons on the Sasaki–Kenmotsu manifold - Sangeetha, M.; Nagaraja, H. G. (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 514.7 We characterize the Sasaki–Kenmotsu manifold by using different kinds of solitons. Thus, we introduce a new type of solitons on the Sasaki–Kenmotsu manifold using a bicontact structure. First, we observe the properties of the Ricci soliton on (η,ω)-Sasaki–Kenmotsu manifold by using bicontact structure. Then we extended the η-Ricci soliton as an (η,ω)-Ricci soliton and a conformal η-Ricci soliton as a conformal (η,ω)-Ricci soliton by using the bicontact structure.